Norslund. En kystboplads fra ældre stenalder - H. Andersen & Malmros, Søren & Claus (Kuml, 1965)
Norslund -A Coastal Settlement from the Old Stone Age Topography. The Norslund Settlement, X 2, is situated just south of the farm Norslund on Norsminde Fjord, 15 km south of Aarhus, at the foot of a south-east facing slope. (fig. 1) 85 sq.m have been excavated (fig. 2). Stratigraphy. The stratigraphy was generally clear, with a practically identical succession over the whole area. South of the main area it was more complex, as will be seen from section H, fig. 5 a-b. The succession in the main area can be briefly described on the basis of section D, fig. 3. Layer 0: Clay soil with artefacts brought up from layer 1 by the plough. Layer 1: Dark grey clay with flint waste, tools and potsherds. South of the dotted line in fig. 2, the clay content increases gradually and artefacts and waste are water-worn, and weathered, which is not the case north of the line. Layer 2: Coarse yellow-brown gravel with artefacts and potsherds. Flint water-worn and weathered. Layer 3: Black clay with high content of flint waste, bone and flint artefacts, animal bones and charcoal. Flint tools weathered. Layer 4: Seashells, shell fragments and sand mixed with flint waste, charcoal, artefacts of bone and flint. Flint tools weathered. Bed-rock everywhere grey moraine clay. All strata have been deposited in connection with a shore zone which has been subject to transgression. Layer 4 thus represents a shore settlement which has moved further and further up the bank in response to the rise in sea-level, whilst layer 3 has been deposited in shallow, calm water which has gradually risen from 1.20 to 1.60 m above present sea-level. Layer 2 seems to have been deposited during a rise in sea-level from 1.60 to 1.75 m. Layer 1 has been partly formed on dry land (north of the dotted line) and partly in shallow water (south of this line). The relationship between sea and shore during the formation of these four strata is seen in fig. 4. Geologically, all strata can be dated as older than the Subboreal transgression's maximum. Artefacts. 1178 flint tools, 133 of bone and antler, 4 of stone and 19 potsherds recovered, besides a large quantity of flint waste and animal bone. The contents of each layer are presented in the figures. Layer 0: Flint artefacts, cf. fig. 6-7. In this layer, the symmetrical, flat-trimmed flake axe is very prominent, cf. fig. 6, no. k 104 and k 560. Fig. 8 illustrates how these axes are distributed according to length, greatest width, width 3 cm from the neck, and thickness. The uniformity of this type is apparent, in particular in thickness, which must reflect quite definite hafting requirements. Several flat-trimmed flake axes show traces of resharpening. The core axes from layer 0 are nearly all symmetrical, with a uni- or bilateral, specially treated edge, fig. 6, no. k 390. Layer 1: Flint artefacts, cf. fig. 9. Flake axes and core axes are of the same types as in layer 0. The other artefact types are not very numerous, but show great regularity of form, cf. fig. 9. 18 potsherds originate from this layer, some thick-walled and coil-built, others thin-walled, fig. 9, no. k 160 and k 411. Layer 2: Flint artefacts, cf. fig. 10. The axes are basically the same as in layer 1, but the core axes are not equipped with a specially treated edge. Particularly numerous are transverse arrow-heads, comprising 70 % of all tools from layer 2. Typical specimens are seen in fig. 10, although oblique arrow-heads as no. 1351 are rare. Six characteristic measurements, as shown in fig. 8, have been recorded for each arrow-head from this layer. Fig. 8 show how the arrowheads are distributed according to these measurements. It will be seen from the histograms that the specimens are grouped around the median values in each case, which indicates that only one type has been aimed at. The majority are made from regular blades with one or two parallel ribs; the ripples on the underside show that the percussion bulb has been immediately outside one edge, cf. fig. 10, no. k 231. A single, thick-walled, coil-built potsherd was found in layer 2. The remaining artefact types resemble those from layers 0 and 1. Layer 3: Flint artefacts, cf. fig. 12-16. In this layer, the atypical core axe is dominant, whilst the flake axe plays only a subsidiary role. The axe material shows that the two types merge imperceptibly, so that an accurate grouping into types is often very difficult, owing to the relatively poor method of working. A tendency towards any particular shape is not recognizable in axes from layer 3. Flake artefacts are also very numerous in layer 3: a selection is shown in fig. 13. Particular note should be made of the flake burins fig. 13 and scrapers, fig. 16, types which were only sporadically represented in layers 0, 1 and 2. Blades and blade tools are numerous and good, and testify to a well-developed and sure technique. Fig 17 shows how blade scrapers and knives with oblique finger-bed are distributed according to angle between the edge and the long axis of the blade. The curve shows why blade scrapers with oblique edge are not separated as a special type, and also distinguished clearly between knives and scrapers. Of blade knives, those with an entire, retouched ridge and crescentshaped outline are worthy of note, fig. 14, no. k 207. Fig. 18 shows the corresponding values of length and breadth for blade knives with oblique finger-bed and crescent-shaped knives. There would appear to be no difference in these dimensions between the two types and they should rather be considered as two forms of the same type. Blade burins are likewise very numerous in layer 3 and very varied, cf. fig. 13. The transverse arrowheads have been treated in the same way as those from layer 2 and the results are presented in fig. 11. A number of the arrow-heads from layer 3 are particularly large. cf. fig. 15, no. x 307, but otherwise do not differ from the other examples. No type grouping has been observed. The raw material for transverse arrow-heads in layer 3 is usually irregular flakes. The underside exhibits a strong convexity, due to the proximity of the percussion bulb to one side, cf. fig. 15, no. k 672. Layer 3: Artefacts of bone and antler, cf. fig. 19-22. Bone tools are represented by 76 pieces, mainly points and their fragments, or unfinished points, fig. 20-22. The type with raised long edges and partly preserved epiphysis, fig. 20, is common. Thick awls, with or without epiphysis, are also common, fig. 20. The preferred raw material for bone tools has been splinters of the long bones of roo- and red deer. The flint-edged spear also occurs, fig. 11, no. 15. A few of the bone tools are remarkable for their ornament, fig. 20-21, no. 14 and 19. 39 antler tools were found, fig. 19. Axes are represented by 5 entire tools and 13 fragments, fig. 19, no. 1-3. The type with a hafting hole through the base and an oblique or transverse edge is the most common. The sawn-off edge portions of such axes show that resharpening has also been employed. Flint-flakers also occur, fig. 19, no. 5-6. Layer 4: Flint artefacts, cf. fig. 23-24. The inventory from this layer agrees very closely with that of layer 3, both in respect of form and distribution. Artefacts of bone and antler, fig. 21, no. 21-24, are not numerous in layer 4, but agree closely with those of layer 3. Of new types, unknown in layer 3, the elbow-bone dagger, fig. 21, no. 24, is notable. Antler axes are absent in layer 4, but edge fragments show that they were extant, although the type cannot be determined. In the same manner, two sawn-off antler tips show that the layer 4 inventory also includes flint flakes. Comparison of artefacts from the various strata. The Norslund settlement does not possess uniform character -both archaeologically and geologically, several phases are present. As Norsminde Fjord in Preboreal and Boreal times has almost certainly been a fresh-water lake, it is important to prove by both geological and archaeological means that all four layers stem from coastal settlements, so that the ecological conditions have been more or less the same for all periods. In the following comparison, all artefacts of organic material have been excluded, only having been present in layers 3-4. Layer 0 has also been excluded, on the grounds that its inventory is of uncertain origin. The cumulative diagram fig. 26 illustrates the percentual distribution of each type, transverse arrow-heads not being represented, however, as the conditions of deposition are very variable on account of their small size. It will be apparent that the four layers fall into two main groups-layers 1-2 and 3-4. Moreover, pottery occurs in layers 1-2, but not in 3-4. Layer 1: As mentioned above, the symmetrical, flat-trimmed flake axe is dominant here, constituting 54 % of the total axes in this layer. The small quantity of other types of flake axe shows that this has been the type aimed at. Also characteristic are the symmetrical core axes with specially treated edge. Core axes constitute only 20 % of the axes in layer 1. Of blade tools, the scraper with concave edge is dominant. The layer is characterized by the rigid type pattern, atypical forms being uncommon. Two types of pottery -thick-walled and thin-walled- are present. The transverse arrow-head is common -in all cases with a straight edge. Layer 2: The symmetrical, flat-trimmed flake axe constitutes 51 % of the axes. Core axes are not supplied with a specially treated edge, but are still evenly worked. Blade tools are of the same types as in layer 1 and show a correspondingly rigid type pattern, rarely departed from. Transverse arrow-heads are regular, and a definite pattern seems to have been aimed at. They nearly all have a straight edge and the raw material is the blade. Thickwalled, coil-built pottery occurs. Layer 3: The atypical core axe is dominant. 72 % of the axes are core axes, compared with about 20 % for layers 1 and 2. Working is poor, and the shapes irregular and atypical. Flake axes are present but not common and only occasionally is the symmetrical, flattrimmed form present. The frequent use of flakes for scrapers and burins is characteristic. Blade tools are good and regular, with specimens of greater technical excellence than those of layers 1 and 2. Blade knives now comprise 15 % of the total inventory, as compared with 6 % in layer 2. Blade burins likewise comprise 15 % of all tools, as against 7.5 % in layer 2 and 6 % in layer I. They cover the whole range of types, although angle burins without transversal chipping are preferred. Transverse arrow-heads are irregular and atypical, usually manufactured from flakes and splinters, in contrast to those from layer 2. The presence of a flint-edged spear is important, occurring for the first time in a dated context in Jutland. Layer 4: The very close resemblance between the inventories of layers 3 and 4 suggests that the same group of people frequented the site during the deposition of both layer 3 and 4. Layer 4 is perhaps a regular kitchen midden and if so it seems to be the oldest in this country. In fig. 27, the relative occurrence of different types of tools in the four layers has been calculated, and further demonstrates the difference between layers 1-2 and 3-4. A corresponding distribution of artefact types has been found in other Danish coastal culture settlements with a cultural succession e. g. Bloksbjerg and Dyrholm. Dating Layer 1: The inventory is identical with that of Dyrholm II (fig. 27), which has been dated to pollen zone VII b by pollen analysis and geologically to the regression between the middle and late Atlantic transgressions. Layer 2: It is not possible to date layer 2 geologically. Archaeologically it seems to fill a gap between Th. Mathiassen's 2nd and 3rd stages of the Jutland Ertebølle Culture, and would thus be approximately contemporaneous with the kitchen middens of Ertebølle and Bjørnsholm in West Himmerland. Layer 3: As this is stratigraphically older than layers 1 and 2, it follows that it must be older than pollen zone VII b, and its content of flint and bone, and complete absence of pottery, indicate a great age. The cumulative diagram, fig. 28, shows agreement in percentual distribution of artefacts between layer 3 and Dyrholm I, and a closer comparison of inventories bears this out. Dyrholm I has been dated geologically as being older than, or contemporaneous with, the beginning of the middle Atlantic transgression, i. e. the transition between pollen zones VII a and VII b. C14-analysis of charcoal from layer 3 gave 3780 ± 120 and 3730 ± 120 B.C. Layer 4: The close archaeological agreement between this and layer 3 suggests that layer 4 is slightly older or roughly contemporaneous. C14-analysis of shell fragments from the base af the layer gave 4470± 130 B.C. -a considerably greater age for layer. 3. The C14-dating is thus in conflict with the archaeological evidence and suggests that not all components of layer 4 are of the same age (shell fragments), but there seems to be good reason for retaining the archaeological dating. Conclusion. The sharp separation in relative occurrence of artefact types between our layers 1-2 and 3-4, and between Dyrholm I and II, is repeated in numerous coastal culture settlements with a cultural succession, all over Denmark, and this separation seems always to coincide with the interval between the beginning of the middle Atlantic transgression and the regression between this and the late Atlantic transgression. A comparison between the Dyrholm I and II inventories reveals that they are not part of a single cultural entity. The characteristic Ertebølle types, such as thick-walled, coil-built pottery, flat-trimmed, symmetrical flake axes and core axes with specially treated edge, are entirely absent in Dyrholm 1 and Norslund layers 3-4. As layer 3 in Norslund is better defined stratigraphically, it is suggested that this cultural group be called the Norslund Group. It seems to have a connection with the Ertebølle Culture in several aspects, although the details of this relationship are not clear. The artefact inventory of the Norslund group is repeated in several sites all over Denmark, but particularly in Jutland. The Ø. Jølby find, which belongs to the Norslund group, provides a connection with even older coastal entities, where the rhombic point occurs. The rhombic point seems to have been in use for a longer period on Zealand than in Jutland, where it is apparently first replaced by the transverse arrow-head. Whether there are regional differences between the early coastal cultures in Denmark cannot be ascertained at this stage. Finally, it should be mentioned that there are traces of even earlier groups around the Norslund settlement, as indicated by the flint edged dagger fig. 25. This is an ex situ find from Flynderhage, about 120 m south-west of Norslund. Its decoration is related to that of the Zealand Kongemose Culture. Claus Malmros & Søren H. Andersen.